Tarihi Romanda Post-Modern Arayışlar - Argunşah, Hülya (Kitabevi, 2002)
New historical novel, which has been pondered and worked on with the theory of intertextuality and other theories, and has gained the dimension of being 'a work of a master', has brought along the senous search for a theory while getting into other and never been written histories. As for the reader who meets a new fictitious world outside the classical historical novel approach, enjoys events, people and their curiosities of strange worlds while trying to find a way through. In this article, we point out the new dimensions of historical novel using the previously mentioned three early works of their kind.
Tracing Post-Modernism in Historical Novel
Keywords: History; Historical Novel; Post-Modernism; Novel; Modern Turkish Literature